SnO2–TiO2 Hybrid Nanofibers for Efficient Dye-Sensitized Solar Cells - Qamar, Wali; Zinab, H. Bakr; Nurul Ain, Manshor; Azhar, Fakharuddin; Rajan, Jose (Elsevier Ltd, 2016)
Pristine SnO2 nanostructures typically result in low open circuit voltage (VOC) <500 mV due to the lower Fermi energy (EF) when employed as a photoanode materials in dye sensitized solar cells (DSSCs). On the other hand, the most successful photoanode material, i.e., TiO2 nanoparticle although provides a high VOC ⩾ 800 mV result in poor charge collection owing to their inferior electron mobility (μn). Herein, we employ nanofiber–nanoparticle composite of SnO2–TiO2 which showed similar VOC and short circuit current density (JSC) to a reference TiO2 based DSSCs. The nanocomposite developed here involves multi-porous SnO2 nanofibers characterized by a lower EF; however, with higher μn and TiO2 nanoparticles of higher EF and lower μn. The TiO2 particles in the pores of SnO2 nanofibers were developed by TiCl4 treatment, whose concentration is optimized for the saturated JSC and VOC. The best performing DSSCs fabricated using the composite electrodes deliver power conversion efficiency (PCE) of ≈7.9% (VOC ≈ 717 mV; JSC ≈ 21 mA cm−2), which is significantly higher than pure SnO2 photoanode with PCE ≈ 3.0% (JSC ≈ 14.0 mA cm−2 and VOC ≈ 481 mV) at similar experimental conditions.